Increased Tumor Ascorbate is Associated with Extended Disease-Free Survival and Decreased Hypoxia-Inducible Factor-1 Activation in Human Colorectal Cancer - Kuiper, Caroline; Dachs, Gabi; Munn, Delwyn; Currie, Margaret; Robinson, Bridget; Pearson, John F.; Vissers, Margreet C. (Frontiers in Oncology, 2014)
Ascorbate is a co-factor for the hydroxylases that regulate the transcription factor hypoxia-inducible factor (HIF)-1, which provides cancer cells with a metabolic and survival advantage in the hypoxic environment of solid tumors. However, whether ascorbate affects tumor development is a highly debated issue. We aimed to determine whether tumor ascorbate was associated with HIF-1 activation and patient disease-free survival. In this study we undertook a retrospective observational analysis of tissue-banked tumor and paired normal tissue from 49 colorectal cancer patients, measuring ascorbate levels, HIF-1α and its downstream gene products BNIP3 and VEGF. Patient survival was monitored for the first six years after surgery. We found that ascorbate levels were lower in tumor tissue compared to normal tissue (p< 0.001) but overall levels varied considerably. HIF-1α, VEGF and BNIP3 were elevated in tumor samples (p< 0.01). There was an inverse relationship between tumor ascorbate content and HIF-1 pathway activation (p=0.002) and tumor size (p=0.018). Higher tumor ascorbate content was associated with significantly improved disease-free survival in the first 6 years after surgery (p=0.006), with 141 - 1,094 additional disease free days. This was independent of tumor grade and stage. Survival advantage was associated with the amount of ascorbate in the tumor, but not with the amount in adjacent normal tissue. Our results demonstrate that higher tumor ascorbate content is associated decreased HIF-1 activation, most likely due to the co-factor activity of ascorbate for the regulatory HIF hydroxylases. Our findings support the need for future studies to determine whether raising tumor ascorbate is possible with clinical intervention and whether this results in modification of hydroxylase-dependent pathways in the tumor.